Profit-Sharing Perception and Service Quality as Determinants of Customers’ Decisions to Use Tadhabur Savings - Putri Izzah Septiani Cindito; Fira Nurafini (International Conference on Islamic Economic (ICIE), 2026)
Customers desires and interests play a role in driving decision-making regarding the use of Islamic bank savings. Customer decisions regarding the use of Islamic bank savings can be influenced by several factors. Differences in customer perceptions of the profit-sharing system in Islamic bank savings occur due to differences in their level of understanding and knowledge regarding the profit-sharing system in Islamic bank savings. The quality of service provided by Islamic banks is also a factor in attracting and retaining Islamic bank customers. This study aims to analyze customer perceptions of the profit-sharing system in Islamic bank savings and the quality of service provided by the bank to customers in relation to customer decisions regarding the use of Islamic bank savings. The sample used in this study was 95 Tadhabur savings customers at BPRS Lantabur Tebuireng, Surabaya Branch. Data collection in this study used questionnaires as primary data which were analyzed using multiple linear regression analysis and processed using SPSS 26. The results of this study indicate that Profit Sharing Perception (X1) has a significant effect on Customer Decisions (Y) in using tadhabur savings at BPRS Lantabur Tebuireng Surabaya Branch and Service Quality (X2) has a significant effect on Customer Decisions (Y) in using tadhabur savings at BPRS Lantabur Tebuireng Surabaya Branch. The t-test results show a significance value for the profit sharing perception variable of 0.005 and the service quality variable of 0.000. This study can be a reference for policies or decisions and provide insight for related parties